Analysis of the 1988 Greenhouse Novel by Pramoedya Ananta Toer with a Postcolonial Approach - Chaniago, Fitri Handayani; Sinaga, Shafira Rahma Dina; Turnip, Putri Firmawindy; Simatupang, Alzyra Fatiha; Lubis, Fitriani (PT FORMOSA CENDEKIA GLOBAL, 2024)
The novel